The Importance of the Study of Social Sciences - Irfan Ahmed Gorshani (`, 2025)
In this paper, the author seeks to discuss how social sciences are very important in the study of and finding solutions to modern issues in the society. The paper, viewed through the prism of an interdisciplinary approach to the study of human behavior, institutional frameworks, and cultural interactions, demonstrates the critical role of social sciences in understanding human behavior and the cultural and institutional frameworks, as well as cultural interactions. The theoretical framework uses the insights of the leading thinkers of the past, such as Weber, Marx, Durkheim, and such modern intellectuals as Sen and Said to show how the social sciences connect the experience of an individual with the history and the structure. Among the most important contributions, we can distinguish the development of critical thinking, the formation of inclusive policies, the encouragement of civic participation, consideration of social inequalities, and the improvement of intercultural awareness. Contextually, the article reveals some systemic issues in the teaching of social science in Pakistan, such as perpetual underfunding, obsolete curriculums and the lack of social value, which all impede the potential of social science to play a role in national development. In the study, the author advocates the immediate reformation of the curricular, faculty, and funding of research to realize the potential strength of social sciences in creating a fairer and more sustainable society. Keywords: Social Sciences, Critical Thinking, Public Policy, Civic Engagement, Social Inequality, Intercultural Understanding, Pakistan, Education Reform, Theoretical Framework, Sustainable Development